Pancreatic stellate cells are activated by proinflammatory cytokines: implications for pancreatic fibrogenesis. Issue 4 (1st April 1999) - Apte, M V; Haber, P S; Darby, S J; Rodgers, S C; McCaughan, G W; Korsten, M A; Pirola, R C; Wilson, J S
Abstract : BACKGROUND: The pathogenesis of pancreatic fibrosis is unknown. In the liver, stellate cells play a major role in fibrogenesis by synthesising increased amounts of collagen and other extracellular matrix (ECM) proteins when activated by profibrogenic mediators such as cytokines and oxidant stress. AIMS: To determine whether cultured rat pancreatic stellate cells produce collagen and other ECM proteins, and exhibit signs of activation when exposed to the cytokines platelet derived growth factor (PDGF) or transforming growth factor β (TGF-β). METHODS: Cultured pancreatic stellate cells were immunostained for the ECM proteins procollagen III, collagen I, laminin, and fibronectin using specific polyclonal antibodies. For cytokine studies, triplicate wells of cells were incubated with increasing concentrations of PDGF or TGF-β. RESULTS: Cultured pancreatic stellate cells stained strongly positive for all ECM proteins tested. Incubation of cells with 1, 5, and 10 ng/ml PDGF led to a significant dose related increase in cell counts as well as in the incorporation of 3 H-thymidine into DNA. Stellate cells exposed to 0.25, 0.5, and 1 ng/ml TGF-β showed a dose dependent increase in α smooth muscle actin expression and increased collagen synthesis. In addition, TGF-β increased the expression of PDGF receptors on stellate cells. CONCLUSIONS: Pancreatic stellate cells produce collagen and other extracellular matrix proteins, and respond to the cytokines PDGF and TGF-β by increased proliferation and increased collagen synthesis. These results suggest an important role for stellate cells in pancreatic fibrogenesis.